Knowledge, Attitude, and Practices toward the Novel Coronavirus Infection in Dental Laboratories in the Kingdom of Saudi Arabia: Cross-Sectional Study - Alsadon, Omar; Alayadi, Haya; Alageel, Omar; Vellappally, Sajith; Almansour, Haitham; Alsarani, Majed (Journal of pharmacy & bioallied science, 2024)
ABSTRACT This study aimed to assess dental technologists/technicians knowledge, attitudes, and practice during the COVID-19 pandemic in Saudi Arabia. This cross-sectional study was conducted among workers in dental laboratories in Saudi Arabia. A validated questionnaire was developed based on previous literature and distributed online. The questionnaire assessed the study population's knowledge, attitude, and practice regarding infection control protocol for COVID-19. Descriptive statistics of categorical variables were conducted. The response rate was 58.3%, where most respondents are male at a rate of 97%. Most of the participants (82%) were aware of the various infection control measures for COVID-19 in a dental laboratory. Forty-eight participants showed a level of knowledge range between 80 and 100%, while 27 and 30 participants reported moderate and low level of knowledge, respectively. Only 67% of the participants strongly agree that dental cast and fabricated/repaired restorations should be transferred in a very close and protective package to control infection. About 70% of participants indicated they always wear protective gear/goggles and should be warned while working in the dental laboratory. As the pumice slurry was utilized frequently to clean and polish the prostheses, 66% of participants agreed that pumice slurry should be always changed regularly. Regarding COVID-19 infection control procedures, dental technologists/technicians showed good knowledge, attitude, and practice; however, considering how infectious the virus is, more measures should be taken into consideration. Effective communication and collaboration between the laboratory and the dental clinic are essential for infection control.